Analisis Pengaruh Perubahan Beban Terhadap Nilai Turbin Heat Rate dan Efisiensi Termal Turbin pada PLTU Cilacap - Febrianto, Muhammad Rafi; Widiawaty, Candra Damis; Wijayanti, Fitri (Politeknik Negeri Jakarta, 2025)
Fluctuations in operating load at the Cilacap Steam Power Plant (PLTU) often cause changes in steam turbine performance that affect generation efficiency and fuel consumption. This study aims to assess the effect of load variations on turbine heat rate, measure changes in thermal efficiency, and analyse their impact on fuel consumption and generation costs. A quantitative correlational method was applied using secondary data from the December 2023 periode, including electrical load parameters, steam flow rate, inlet-outlet enthalpy, and generator output. Heat rate and thermal efficiency calculations were performed based on thermodynamic formulas, while fuel consumption and cost analysis were conducted through comparisons of values per kWh. The results show that an increase in operating load consistently reduces the heat rate and improves thermal efficiency, meaning that steam energy is utilised more optimally. Additionally, fuel consumption and generation costs tend to decrease as the load approaches optimal conditions. These findings underscore the importance of maintaining the operating load within an appropriate range to maximise energy efficiency, reduce fuel consumption, and minimise electricity production costs at the Cilacap Coal-Fired Power Plant